A conserved arginine/lysine-based motif promotes ER export of KCNE1 and KCNE2 to regulate KCNQ1 channel activity. Issue 1 (1st January 2019) - Hu, Bin; Zeng, Wen-Ping; Li, Xia; Al-Sheikh, Umar; Chen, San-You; Ding, Jiuping
ABSTRACT: KCNE β-subunits play critical roles in modulating cardiac voltage-gated potassium channels. Among them, KCNE1 associates with KCNQ1 channel to confer a slow-activated I Ks current, while KCNE2 functions as a dominant negative modulator to suppress the current amplitude of KCNQ1. Any anomaly in these channels will lead to serious myocardial diseases, such as the long QT syndrome (LQTS). Trafficking defects of KCNE1 have been reported to account for the pathogenesis of LQT5. However, the molecular mechanisms underlying KCNE forward trafficking remain elusive. Here, we describe an arginine/lysine-based motif ([R/K](S)[R/K][R/K]) in the proximal C-terminus regulating the endoplasmic reticulum (ER) export of KCNE1 and KCNE2 in HEK293 cells. Notably, this motif is highly conserved in the KCNE family. Our results indicate that the forward trafficking of KCNE2 controlled by the motif (KSKR) is essential for suppressing the cell surface expression and current amplitude of KCNQ1. Unlike KCNE2, the motif (RSKK) in KCNE1 plays important roles in modulating the gating of KCNQ1 in addition to mediating the ER export of KCNE1. Furthermore, truncations of the C-terminus did not reduce the apparent affinity of KCNE2 for KCNQ1, demonstrating that the rigid C-terminus of KCNE2 may not physically interact with KCNQ1. In contrast, the KCNE1 C-terminus is critical for its interaction with KCNQ1. These results contribute to the understanding of the mechanisms of KCNE1 and KCNE2 membrane targeting and how they coassemble with KCNQ1 to regulate the channels activity.